Preparation and characterization of some Heterocyclic compounds linked to graphene oxide and study of their effect to remove Cd (II) and Pb (II) from industrial wastewater (Journal of the College of Basic Education, 2026)
In this study, several heterocyclic compounds were prepared and combined with graphene oxide to produce composite materials with high adsorption efficiency, exceeding that of each individual component. This is attributed to the unique surface properties of graphene oxide, particularly the presence of functional groups such as hydroxyl, carboxyl, and epoxy groups, which facilitate bonding with the prepared compounds. Furthermore, the heterocyclic compounds possess donor atoms such as nitrogen and sulfur, enhancing their ability to form strong coordinate bonds with heavy metal ions. The efficiency of the prepared composite materials in removing cadmium (II) (Cd²⁺) and palladium (II) (Pd²⁺) ions from contaminated aqueous solutions simulating industrial wastewater, was investigated. Adsorption experiments were conducted under various time and pH conditions, with mass and temperature constants, and the concentrations of residual ions were determined using atomic absorption spectroscopy. Advanced analytical techniques, including FTIR, XRD, AFM, and FESEM, were used to characterize the composite materials to determine their chemical composition, surface properties, and morphology. The results demonstrated a significant improvement in the adsorption efficiency of the composite materials compared to the individual materials, confirming their potential as effective materials for treating water contaminated with heavy metals